Research on Boiling Heat Transfer Characteristics and Visualization of Refrigerant in Rectangular Microchannels - Deng Cong; Luo Xiaoping; Feng Zhenfei; Zhang Ruida (Zhileng xuebao)
To investigate the characteristics of flow boiling and heat transfer in microchannels, experiments was carried in rectangular microchannels using refrigerant R22 as working fluid, and visualization experiment was performed using high speed camera. The results show that: heat transfer coefficient is barely influenced by the mass flow rate, but it increases rapidly along with the increment of the heat flux. The smaller the size of microchannels, the better heat transfer effects. Under the same condition of heat flux and mass flow rate, the values of heat transfer coefficient in 0.92 mm and 1.33 mm microchannels increase by 25% and 12% respectively compared to that of 2 mm. A new correlation based on the models of Oh H K et al [15] and Yun R et al [7] is shown to provide very good predictions, evidenced by an overall MAE of 8.8%. Wavy vapor layer was observed under the critical heat flux in visualization experiment.